Race/ethnicity and challenges for optimal insulin therapy. (May 2021) - do Vale Moreira, Nayla Cristina; Ceriello, Antonio; Basit, Abdul; Balde, Naby; Mohan, V.; Gupta, Ritesh; Misra, Anoop; Bhowmik, Bishwajit; Lee, Moon K.; Zuo, Hui; Shi, Zumin; Wang, Youfa; et al.
Highlights: Insulin therapy recommendations have been largely developed from trials in white populations. Higher therapeutic failures in non-white populations are reported. Insulin resistance, insulin sensitivity, glycaemic response and glycaemic control vary by ethnicity. These disparities may lead to different insulin requirements. Comprehensive updated insulin therapy guidelines by ethnicity are urgently needed. Abstract: Aims: We aimed to review insulin dosing recommendations, insulin regulation and its determinants, glycaemic response to carbohydrates, and the efficacy and safety of insulin therapy in different races/ethnicities. Methods: We searched for articles in PubMed and Google Scholar databases up to 31 March 2021, with the following keywords: "ethnicity", "diabetes", "insulin", "history of insulin", "insulin therapy", "food/rice", "carbohydrate intake", "insulin resistance", "BMI", "insulin dosing", "insulin sensitivity", "insulin response", "glycaemic index", "glycaemic response", "efficacy and safety", with interposition of the Boolean operator "AND". In addition, we reviewed the reference lists of the articles found. Results: The differential effect of race/ethnicity has not yet been considered in current insulin therapy guidelines. Nevertheless, body size and composition, body mass index, fat distribution, diet, storage, and energy expenditure vary significantly across populations. Further, insulin sensitivity, insulin response, and glycaemic response to carbohydrates differ by ethnicity. These disparities may lead to different insulin requirements, adversely impacting the efficacy and safety of insulin therapy among ethnic groups. Conclusions: Race/ethnicity affects glucose metabolism and insulin regulation. Until now, international guidelines addressing racial/ethnic-specific clinical recommendations are limited. Comprehensive updated insulin therapy guidelines by ethnicity are urgently needed.